2003
DOI: 10.1063/1.1591232
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembled subnanolayers as interfacial adhesion enhancers and diffusion barriers for integrated circuits

Abstract: Preserving the structural and functional integrity of interfaces and inhibiting deleterious chemical interactions are critical for realizing devices with sub-50 nm thin films and nanoscale units. Here, we demonstrate that ∼0.7-nm-thick self-assembled monolayers (SAMs) comprising mercapto-propyl-tri-methoxy-silane (MPTMS) molecules enhance adhesion and inhibit Cu diffusion at Cu/SiO2 structures used in device metallization. Cu/SAM/SiO2/Si(001) structures show three times higher interface debond energy compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
81
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(82 citation statements)
references
References 9 publications
1
81
0
Order By: Relevance
“…XPS spectra from Cu fracture surfaces show the Si 2p corelevel band at ~102.5 eV characteristic of silyl alkyl moieties in the organosilane, in contrast to the silica Si 2p signature at ~103.5 eV seen on silica fracture surfaces (see Fig. 3), confirming that delamination occurs via siloxane bond fissure at the NML-silica interface 10 . This delamination pathway remains characteristics are similar to, but consistently lower than, that from nanoindentation (Fig.…”
Section: Methodsmentioning
confidence: 85%
See 2 more Smart Citations
“…XPS spectra from Cu fracture surfaces show the Si 2p corelevel band at ~102.5 eV characteristic of silyl alkyl moieties in the organosilane, in contrast to the silica Si 2p signature at ~103.5 eV seen on silica fracture surfaces (see Fig. 3), confirming that delamination occurs via siloxane bond fissure at the NML-silica interface 10 . This delamination pathway remains characteristics are similar to, but consistently lower than, that from nanoindentation (Fig.…”
Section: Methodsmentioning
confidence: 85%
“…The Ta layer was used to offset poor Cu-epoxy adhesion. Our earlier works 9,10 have shown that the NML is strongly bound to the copper overlayer via thioligation and bond-breaking occurs exclusively at the NML-silica interface through the fissure of Si-O-Si bridges formed during molecular assembly (Fig. 1a).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…476 More recently, SAMS have been demonstrated as Cu diffusion barriers, [477][478][479] low-k ILD pore sealants, 480 Cu surface passivation layers, 481 and Cu/ILD adhesion promoters. 482,483 Due these successes and thicknesses <2-3 nm, SAMS are extremely attractive for meeting the ITRS forecast for <2 nm DBs. However in head-to-head comparisons with state-of-the-art TaN/Ta Cu diffusion barriers, SAMS have exhibited order of magnitude lower lifetimes in Cu-MIS TDDB testing indicating that SAMS may not be able to completely meet low-k/Cu interconnect reliability requirements.…”
Section: 15mentioning
confidence: 99%
“…[3] As feature sizes decrease to below 100 nm, traditional interfacial barrier layers such as Ti/TiN and Ta/TaN are no longer suitable because they do not provide adequate performance as thicknesses reduce to 20 nm or less in order to maximize the space available for a copper conductor. [4] Recently, Ramanath et al [5,6] demonstrated the use of near-zero thickness (<2 nm thick) self-assembled molecular monolayers (SAMs) as candidates for ultrathin barrier layers to prevent Cu diffusion into SiO 2 -based dielectrics. They proposed that, due to its superior barrier property at the near-zero thickness, SAMs should be preferred over the traditional diffusion barriers of Ta, TaN, and TiN deposited onto Si/SiO 2 by conventional vapor deposition techniques.…”
Section: Introductionmentioning
confidence: 99%